Individual differences in parasympathetic functioning across social stressor tasks: Relations with child and parent anxiety. - Bui, Hong N. T.; Chronis‐Tuscano, Andrea; Shakiba, Nila; Rubin, Kenneth H.; Perlstein, Samantha; Lorenzo, Nicole E.; Novick, Danielle R.; Danko, Christina M.; Dougherty, Lea R.; Wagner, Nicholas J. (Infant & Child Development, 2024)
Children with elevated behavioural inhibition (BI) show context‐inappropriate fear and dysregulated RSA across stressor tasks. However, few studies have examined dynamic RSA within tasks and relations to parent and child anxiety. Using piecewise growth modelling and multimethod baseline data from an intervention study of 151 3.5–5‐year‐old children and their parents, we examined relations between child social anxiety (SA), parent anxiety and their interaction in predicting children's RSA across social stressor tasks (e.g. learning about unfamiliar peers, Trier Social Stress). Within the sample, 49.63% of children were reported to be White, non‐Hispanic/Latine (n = 67), 22% multiracial (n = 31), 14.81% Asian/Pacific Islander (n = 20) and 12.59% Black/African‐American (n = 17). Furthermore, 64.44% of the parents were reported to be White, non‐Hispanic/Latine (n = 87), 20% Asian/Pacific Islander (n = 27), 13.33% Black/African‐American (n = 18) and 2.22% multiracial (n = 3). Children showed differentiated RSA reactivity and recovery within an anticipatory social learning task based on their level of clinically appraised SA. Relations between child SA and RSA across tasks was moderated by parent anxiety, specifically for dyads matched in anxiety. Findings provide support for the potential influence of both child and parent anxiety on children's parasympathetic nervous system (PNS) responses across specific self‐regulatory tasks.